Some uniformly starlike functions with varying arguments - Vijaya, K.; Murugusundaramoorthy, G. (Tamkang Journal of Mathematics, 2004)
In this paper two new subclasses of starlike functions that are analytic and normalized in the open unit disc with varying arguments is introduced. For functions in these classes we obtained coefficient bound, distortion results and the extreme points.